Dementia and Mild Cognitive Impairment Identification in Illiterate and Low-Educated People: Systematic Review About the Use of Brief Cognitive Screening Tools - Jonathan Adrián Zegarra-Valdivia; Brenda Chino; Kuripacha Tituana; Lina Zapata-Restrepo; María Martha Unaucho; Milton Lopez-Norori; Carmen Paredes-Manrique; Nilton Custodio (Behavioral Sciences)
The rising prevalence of dementia, particularly in low-income and developing countries, highlights the urgent need for effective cognitive screening tools. However, the existing tools often fail to address the unique needs of low-educated and illiterate populations, leading to diagnostic disparities. This review aimed to evaluate cognitive screening tests and domains employed globally to detect mild cognitive impairment (MCI) and dementia in low-educated and illiterate older adults. Following the PRISMA guidelines, Searches were performed in Web of Science, Scopus, and PubMed, targeting studies from January 2000 to 2023 involving adults over 45 years old. Of 1611 studies identified, 27 met the inclusion criteria and underwent pair review. The results revealed that most studies preferred adapting the existing tools to local languages over developing culturally tailored instruments. Twelve cognitive tests specifically designed for low-educated populations were identified, with the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) being the most utilized, despite their educational biases. Adjusting the cutoff points improved detection (e.g., MoCA: sensitivity 82.5%, specificity 82%). Notably, the Rowland Universal Dementia Assessment Scale (RUDAS) demonstrated superior performance for low-educated groups (sensitivity 89% and specificity 93%). The findings underscore the critical need for region-specific cognitive batteries that integrate functional assessments, ensuring equitable and accurate diagnosis across diverse educational backgrounds.